Rising socioeconomic disparities in childhood overweight and obesity in Belgium - Sabine Drieskens; Rana Charafeddine; Stefanie Vandevijvere; Robby De Pauw; Stefaan Demarest (BMC, 2024)
Abstract Background Childhood overweight, especially obesity, significantly impacts children's health and poses an increased risk of adult-onset diseases. This study aims to analyse the evolution of childhood overweight and obesity in Belgium from 1997 to 2018 and assess its variation across parental socioeconomic status (SES). Methods The Health Interview Survey, a cross-sectional survey representative of the Belgian population, has been conducted since 1997, with the latest survey conducted in 2018. This study focuses on children aged 2-17 years. Body Mass Index (BMI, kg/m²) was derived from self-reported data, supplemented with proxy reports for children under 15 years old. Overweight and obesity were classified using age/sex-specific cut-off points. Highest parental educational level served as the indicator of SES. In addition to reporting the overall prevalence and the 95% confidence interval (95%CI) of childhood overweight and obesity by year, this study examines the absolute difference in prevalence between SES groups (low minus high) and calculates the Odds Ratio (OR, adjusted for age and sex) to evaluate the relative difference. Results The overall prevalence of childhood overweight rose from 13.6% (95%CI = 11.2-16.1%) in 1997 to 18.9% (95%CI = 16.3-21.5%) in 2018; while it remained stable for obesity, fluctuating between 5.4% and 6.3% over the same period. This increase was more pronounced among children with low SES compared to those with high SES. Consequently, the absolute difference between children with low and high SES increased over time from 8.0% points (pp) in 1997 to 14.9 pp in 2018 for overweight, and from 3.1 pp to 6.8 pp for obesity. In terms of relative inequalities, overall, children with low SES exhibited significantly higher odds of overweight and of obesity than those with high SES (OR varying between 2 à 3 for overweight and between 2 and 4 for obesity). Conclusions The escalating disparities over time highlight SES as a significant risk factor for childhood overweight and obesity. Addressing these inequalities requires interventions such as providing healthy meals and increasing sports opportunities at school. Additionally, it is recommended to regulate fast food outlets near schools and limit unhealthy food marketing, particularly because children with low SES are more exposed to such influences.